2021
DOI: 10.1111/ddg.14501_g
|View full text |Cite
|
Sign up to set email alerts
|

Gibt es eine Überbehandlung von Melanompatienten am Ende ihres Lebens? Ergebnisse einer multizentrischen Studie an 193 Melanompatienten

Abstract: Wo ist der Patient verstorben?Results: 193 patients from four dermato-oncological centers were included. More than 60 % of the patients had ECOG ≥ 2 and most of them received immune checkpoint inhibitors (ICI) or targeted therapies (TT). 41 patients benefited from the last therapy in terms of radiological and laboratory findings or state of health. Although ECOG was worse in the TT cohort compared to the ICI group, the proportion of patients benefiting from the last therapy with TT was significantly higher and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Indeed, oncological patients, in particular, often experience overtherapy at the end of life that is not helpful for the affected patients, but makes dying in accordance with their own wishes more difficult and also places an unnecessary burden on the health system. 10,11 Since 2017, the advance care planning consultation offer for residents of nursing institutions and for people with disabilities is covered by statutory health insurance according to § 132g SGB V. 12 Concerning oncological diseases, it has been shown that advance care planning (ACP), in particular, is associated with a reduction in hospitalizations and the often unwanted death in hospital. 13 The German AWMF S3 guideline on "Diagnosis, therapy, and follow-up of melanoma"provides little information on palliative care of patients with incurable disease, but refers to the S3 guideline on "Palliative care for patients with incurable cancer" of the German Society for Palliative Medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, oncological patients, in particular, often experience overtherapy at the end of life that is not helpful for the affected patients, but makes dying in accordance with their own wishes more difficult and also places an unnecessary burden on the health system. 10,11 Since 2017, the advance care planning consultation offer for residents of nursing institutions and for people with disabilities is covered by statutory health insurance according to § 132g SGB V. 12 Concerning oncological diseases, it has been shown that advance care planning (ACP), in particular, is associated with a reduction in hospitalizations and the often unwanted death in hospital. 13 The German AWMF S3 guideline on "Diagnosis, therapy, and follow-up of melanoma"provides little information on palliative care of patients with incurable disease, but refers to the S3 guideline on "Palliative care for patients with incurable cancer" of the German Society for Palliative Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Care planning has the aim to enable people to deal with end‐of‐life questions and especially with limits of nursing and medical measures and interventions, as well as palliative medical support. Indeed, oncological patients, in particular, often experience overtherapy at the end of life that is not helpful for the affected patients, but makes dying in accordance with their own wishes more difficult and also places an unnecessary burden on the health system 10,11 . Since 2017, the advance care planning consultation offer for residents of nursing institutions and for people with disabilities is covered by statutory health insurance according to § 132g SGB V 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Gerade onkologische Patienten erfahren nämlich am Lebensende oftmals eine Übertherapie, die für die Betroffenen nicht hilfreich ist, sondern das Sterben nach eigenen Vorstellungen erschwert und zusätzlich auch das Gesundheitssystem unnötig belastet. 10,11 Das Beratungsangebot der Versorgungsplanung wird seit 2017 für Menschen in Pflegeeinrichtungen und Menschen mit Behinderungen gemäß § 132g SGB V von den gesetzlichen Krankenkassen übernommen. 12 In der onkologischen Erkrankungssituation konnte gezeigt werden, dass besonders die vorausschauende Versorgungsplanung in Form von Advance Care Planning (ACP) mit einer Reduktion von Hospitalisierungen sowie dem, oftmals nicht gewollten, Versterben im Krankenhaus assoziiert ist.…”
Section: Introductionunclassified
“…Bei der Versorgungsplanung soll Menschen ermöglicht werden, sich mit Fragen und insbesondere Grenzen pflegerischer und medizinischer Maßnahmen und Interventionen sowie palliativmedizinischer Unterstützung auseinanderzusetzen. Gerade onkologische Patienten erfahren nämlich am Lebensende oftmals eine Übertherapie, die für die Betroffenen nicht hilfreich ist, sondern das Sterben nach eigenen Vorstellungen erschwert und zusätzlich auch das Gesundheitssystem unnötig belastet 10,11 . Das Beratungsangebot der Versorgungsplanung wird seit 2017 für Menschen in Pflegeeinrichtungen und Menschen mit Behinderungen gemäß § 132g SGB V von den gesetzlichen Krankenkassen übernommen 12 .…”
Section: Introductionunclassified